L-Cysteine Ameliorates Ultra-low Temperature Preservation Induced Cryodamage of Murrah Buffalo Spermatozoa - Alam, Kabir; Srivastava, Sushant; Sakhahari, Daund Sushant; Kumar, Rajesh; Verma, Abhishek Kumar; Verma, Sanjeev Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was carried out with the aim to evaluate the effect of L-cysteine hydrochloride as an antioxidant on the in-vitro fertilizing potentials of buffalo spermatozoa through Hypo-osmotic swelling test (HOST) and sperm mucus penetration test (CMPT). Thirty-six ejaculates were collected from six Murrah bulls. The semen samples were divided into two groups, and were extended with Tris-citric acid-fructose-egg-yolk-glycerol (TFYG) extender without additive, i.e., control (C) extender and with L-cysteine hydrochloride (1.0 mM) i.e. treatment (T) extender. The HOST and CMPT were evaluated at both post-dilution and post-thaw stages. The cysteine hydrochloride fortified group (T) recorded a significant (p<0.05) improvement in HOS-positive spermatozoa and the distance traveled by vanguard spermatozoa as compared to control group. In conclusion, cysteine hydrochloride improves post-thawed sperm functional parameters in Murrah bull semen, indicating that incorporating cysteine hydrochloride into a semen extender may improve fertility.